NCOG-01. PRESERVATION OF NEUROCOGNITIVE FUNCTION (NCF) WITH HIPPOCAMPAL AVOIDANCE DURING WHOLE-BRAIN RADIOTHERAPY (WBRT) FOR BRAIN METASTASES: PRELIMINARY RESULTS OF PHASE III TRIAL NRG ONCOLOGY CC001. (5th November 2018) - Gondi, Vinai; Pugh, Stephanie; D Brown, Paul; Wefel, Jeffrey; Gilbert, Mark; Bovi, Joseph; Robinson, Cliff; Tammie, Benzinger; Tome, Wolfgang; Armstrong, Terri; Bruner, Deborah; Khuntia, Deepak; et al.
Abstract: PURPOSE: NRG CC001, a phase III trial of WBRT plus memantine with or without hippocampal avoidance, sought to evaluate the neuro-protective effects of avoiding the hippocampus using intensity-modulated radiotherapy. METHODS: Adult patients with brain metastases were stratified by RPA class and receipt of prior radiosurgery/surgery and randomized to WBRT+memantine (WBRT+M) versus hippocampal-avoidant WBRT+memantine (HA-WBRT+M) (30Gy in 10 fractions). Standardized NCF tests were performed at baseline, 2, 4, 6, and 12 months. The primary endpoint was time to NCF failure, defined as decline on at least one of the following tests using the reliable change index: Hopkins Verbal Learning Test-Revised, Trail Making Test, or Controlled Oral Word Association. Cumulative incidence was used to estimate time to NCF failure (death without NCF failure was treated as competing risk) with between-arms differences tested using Grays test. To detect an 11% absolute reduction in 6-month NCF failure, 382 analyzable patients were required for 90% power with two-sided =0.05. Due to possible non-compliance, the sample size was increased by 25% (510 patients). RESULTS: From July 2016 to March 2018, 518 patients were randomized. Median age was 61.5 years. Median follow-up for alive patients was 6.1 months. Treatment arms did not differ in grade3 toxicity, overall survival, intracranial progression, or baseline NCF. Time to NCF failure was significantly longer in favor of HA-WBRT+M (p=0.012). The 6-month NCF failure rates were 69.1% (95% CI:61.8–75.3%) vs. 58.0% (95% CI:50.2–64.9%) for WBRT+M vs. HA-WBRT+M, respectively. After adjusting for stratification factors, HA-WBRT+M (hazard ratio (HR)=0.73, 95%CI:0.56–0.94, p=0.016) and age 61 years (HR=0.61, 95%CI:0.46–0.81, p=0.0006) remained significant. CONCLUSION: Preliminary analysis confirms that conformal avoidance of the neuro-regenerative hippocampal stem cell compartment during WBRT preserves neurocognitive function while achieving similar intracranial control and survival. Supported by grants UG1CA189867 (NCORP), U10CA180868 (NRG Oncology Operations), DCP from the National Cancer Institute.